(untitled) (REMUNOM, 2024)
Remineralizer is a residue from rock grinding that contains nutrients for plants and compounds that act as soil fertility improvers. The application of ground rock is a technique used in soil fertilization, which can be a complementary alternative to industrialized fertilizers. Based on this hypothesis, the objective of this study was to evaluate the nutritional contents in samples of Quartzarenic Neosol, Pétrico Plintosol and Haplic Plintosol in floodplain conditions, fertilized with a remineralizer. The experimental design used was completely randomized (DIC), in a double factorial scheme (3x5), consisting of three types of soil (typical Ortic Quartzarene Neosol, argisolic Concretionary Pétrico Plintosol and typical Dystrophic Haplic Plintosol in floodplain conditions), and five doses of rock extracted and ground in Peixe - TO (0, 1, 2, 3 and 4 t ha-1 of remineralizer), with four replications. The experimental units were subjected to 60 days of incubation, following the methodology of Machado, (2017). The levels of Ca, P, K, Mg, H+Al, and Al and the pH, CTC, SB and EC values ​​in the soil were evaluated. A positive association was found between SB, Ca, Al, EC, Mg, CTC and pH for the floodplain soil, with better contributions with the application of a dose of 3 tons per hectare of remineralizer. Results also demonstrate that soils with higher K and P contents have lower H+Al content, and vice versa. The Pétrico Plintosol, with the application of a dose of 1 ton of remineralizer per hectare, obtained the highest values ​​of K and P. In contrast, lower values ​​of these nutrients were observed in the Quartzarenic Neossolo, which obtained higher levels of H+Al. The results obtained confirm the practice of rocking as an alternative for replacing nutrients in a complementary way, to maintain the fertility of fragile soils.